2018
DOI: 10.1074/jbc.ra118.002951
|View full text |Cite
|
Sign up to set email alerts
|

MgATP hydrolysis destabilizes the interaction between subunit H and yeast V1-ATPase, highlighting H's role in V-ATPase regulation by reversible disassembly

Abstract: Vacuolar H-ATPases (V-ATPases; VV-ATPases) are rotary-motor proton pumps that acidify intracellular compartments and, in some tissues, the extracellular space. V-ATPase is regulated by reversible disassembly into autoinhibited V-ATPase and V proton channel sectors. An important player in V-ATPase regulation is subunit H, which binds at the interface of V and V H is required for MgATPase activity in holo-V-ATPase but also for stabilizing the MgADP-inhibited state in membrane-detached V However, how H fulfills t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 56 publications
2
30
0
1
Order By: Relevance
“…We have recently observed that transient MgATP hydrolysis on V1Hwt, which, unlike wild type V1, is not in the MgADP inhibited state (Fig. 2B), lowers H's affinity for V1, and we reasoned Role of subunit H in V-ATPase assembly that this destabilization of the V1-H interaction is caused by MgATP hydrolysis driven conformational changes at the catalytic sites and the central (DF) and peripheral stalks (EG1-3) (24). We propose that an allosteric structural change at the open catalytic site driven by release of inhibitory MgADP from the closed catalytic site in autoinhibited, wild type V1 (by a yet unknown mechanism) leads to the detachment of HCT from its inhibitory position at the open site, making it in turn available to bind aNT on Vo.…”
Section: Release Of Inhibitory Mgadp May Cause Detachment Of Hct Frommentioning
confidence: 96%
See 3 more Smart Citations
“…We have recently observed that transient MgATP hydrolysis on V1Hwt, which, unlike wild type V1, is not in the MgADP inhibited state (Fig. 2B), lowers H's affinity for V1, and we reasoned Role of subunit H in V-ATPase assembly that this destabilization of the V1-H interaction is caused by MgATP hydrolysis driven conformational changes at the catalytic sites and the central (DF) and peripheral stalks (EG1-3) (24). We propose that an allosteric structural change at the open catalytic site driven by release of inhibitory MgADP from the closed catalytic site in autoinhibited, wild type V1 (by a yet unknown mechanism) leads to the detachment of HCT from its inhibitory position at the open site, making it in turn available to bind aNT on Vo.…”
Section: Release Of Inhibitory Mgadp May Cause Detachment Of Hct Frommentioning
confidence: 96%
“…Reversible disassembly requires the concerted breakage and reforming of subunit-subunit interactions, most of which involve the peripheral stator subunits E,G,H,C, and aNT. Using purified subunits and their domains, we found that while the head domain of C (Chead) and the N-terminal domain of H (HNT) bind EG with nanomolar affinity, C's foot domain (Cfoot), EG and H, all bind aNT weakly (23,24). It was therefore suggested that the V1-Vo interface is constituted by multiple low-affinity interactions that result in high-avidity binding.…”
Section: Role Of Subunit H In V-atpase Assemblymentioning
confidence: 99%
See 2 more Smart Citations
“…Este mecanismo resulta na interrupção da hidrólise do ATP e do transporte de prótons, sendo geralmente desencadeado em resposta à diminuição dos níveis de glicose Forgac, 2007;Cipriano et al, 2008;Jefferies et al, 2008;Toei et al, 2010). A dissociação dos domínios é importante para economia de energia quando em baixas concentrações de ATP e glicose, uma vez que o domínio V1 isolado não realiza a hidrolise do ATP e o domínio V0 é bloqueado durante o processo para que não ocorra o transporte passivo de prótons (Parra et al, 2000;Diab et al, 2009;Benlekbier et al, 2012;Couoh-Cardel & Wilkens, 2015;Sharma et al, 2018;Hayek et al, 2019). Durante o processo de dissociação, a subunidade C tem um papel fundamental para que o processo ocorra e se separa completamente dos domínios V1 e V0 (Iwata et al, 2004;Jefferies et al, 2008;Tabke et al, 2014).…”
Section: Introdução__________________________________________________unclassified